Problems of Training Qualified Personnel in the Art of Cinema, Television and Radio (Texas Journal of Multidisciplinary Studies, 2023)
The article talks about the art of cinema and its educational significance, which appeared at the beginning of the X1X century and went through a huge development path. To date, computer technology has set the stage for a great evolutionary period in cinema to be overcome at short opportunities. But for the development of Soha, our shortcomings, which are allowed today, are also sufficient. The article will talk about the fact that we need to carry out the work of talay for the cultivation of qualified personnel, the attention of the heads of state